A new neuropsychological tool for simultaneous reading and executive functions assessment: initial psychometric properties - de Oliveira, Vinícius Figueiredo; Vial-Martins, Jéssica; Pinto, André Luiz de Carvalho Braule; Fonseca, Rochele Paz; Malloy-Diniz, Leandro Fernandes (Frontiers in psychology, 2024)
The development of reading and complex executive functions is fundamental for achieving social, academic, and professional success. So far, there is no single neuropsychological instrument that comprehensively assesses the domains of inhibitory control, cognitive flexibility, working memory, and reading comprehension. To assess executive functions related to reading, the "Assessment of Reading and Executive Functions" (AREF) was developed. In this study, we show initial evidence of validity and reliability for four subtests - Graphophonological-Semantic Flexibility, Inhibitory Control, Flexibility, and Working Memory. A total of 93 students from 4th to 9th grade, aged 8-14, in public ( = 61) and private ( = 32) schools were evaluated. Tasks from the AREF instrument, as well as measures of reading comprehension, inhibitory control, cognitive flexibility, working memory, and intelligence, were administered. Correlations between AREF scores and the other measures were performed to assess external construct validity. Performance differences between school groups on AREF subtests were analyzed using ANOVA, t-test, and Mann-Whitney tests, and the internal consistency of the instrument's tasks was evaluated using Cronbach's alpha coefficient. The scores of the AREF subtests demonstrated significant positive correlations with reading measures (ranging from 0.339 to 0.367) and executive functions (ranging from 0.209 to 0.396). Significant differences were found in the performance of some AREF tasks when comparing individuals from public and private schools, as well as between 4th and 5th graders compared to students in higher grades. The internal consistency of the tasks was low for Graphophonological-Semantic Flexibility (Cronbach's α = 0.566), moderate for Inhibitory Control and Flexibility (Cronbach's α = 0.768), and high for Working Memory (Cronbach's α = 0.881). The results provide initial evidence of construct validity and reliability for the AREF subtests. It is expected that this new neuropsychological test will contribute to the assessment of reading skills and executive functions, assisting in guiding clinical and educational interventions for individuals with and without neurodevelopmental disorders.